Après le soixante-dixième anniversaire de 1936 - François Godicheau (Mélanges de la Casa de Velázquez, 2008)
To draw up a balance of historiography on the seventieth anniversary of the civil war would require more than a mere review of the books published in 2006. The issue of the war of 1936 has taken a central place in the public arena and in debate among citizens, to the extent that professional historians today are increasingly faced with manifold demands that have to be attended to in any analysis of historical production. An examination of two broad syntheses on the history of the war serves to measure not only the progress of knowledge but also the interpretative limits of the classical account of the conflict, which is now questioned by several original works. These propose an approach which, if accompanied by a systematic discussion on how the identity of history’s actors is forged and how historians handle language, could pave the way for a genuinely new approach to the history of this war, as long as there is a real debate.